Teacher Perspective: Implementation of Contextual Teaching and Learning Model - Nurjehan, Rizki; Khairil Ansari; Yusnadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Research on Teacher Perspectives in the implementation of the Contextual Teaching and Learning model aims to analyze teachers' views on the implementation of the Contextual Teaching and Learning model. This research analyzes the difficulties, obstacles, advantages and disadvantages during the process of implementing the Contextual Teaching and Learning model. This research uses a qualitative descriptive method using observation sheets and questionnaires to collect the required information data and process it into the findings described. The findings obtained from the research are that there are obstacles to implementing the Contextual Teaching and Learning model at the Learning Community stage of 50% compared to the level of difficulty at other stages such as constructivism 20%, inquiry 10%, questioning 5%, modeling 5%, reflection 5% and authentic assessment 5%. Furthermore, it can be seen that the lowest level of implementation was in the Learning Community component, with 55 people answering that it was not implemented. Furthermore, in other components, namely constructivism, inquiry, questionnaire, modeling, reflection and authentic assessment, it was seen that an average of 15 to 20 people answered that it had not been implemented. So the research results conclude that there are obstacles to the implementation of the Learning Community stages in the Contextual Teaching and Learning model. The difficulty of implementing the Learning Community stages by teaching staff.